2015
DOI: 10.1021/acs.chemrev.5b00434
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Active Site Directed Tools for Studying Human Caspases

Abstract: Caspases are proteases of clan CD and were described for the first time more than two decades ago. They play critical roles in the control of regulated cell death pathways including apoptosis and inflammation. Due to their involvement in the development of various diseases like cancer, neurodegenerative diseases or autoimmune disorders, caspases have been intensively investigated as potential drug targets, both in academic and industrial laboratories. This review presents a thorough, deep, and systematic asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 432 publications
(1,033 reference statements)
5
77
0
Order By: Relevance
“…In our opinion, the S2 pocket is crucial for distinguishing between granzyme B and caspases since it is the only position in which these enzymes possess distinct specificity. With our peptide library screening of GrB, we confirmed that it recognizes glutamic acid at P3 and shares this feature with caspases 10,17,22,29 . The carboxyl group of glutamic acid interacts with Lys192 and Asn218 in the GrB S3 pocket, consistent with GrB specificity.…”
Section: Discussionsupporting
confidence: 55%
“…In our opinion, the S2 pocket is crucial for distinguishing between granzyme B and caspases since it is the only position in which these enzymes possess distinct specificity. With our peptide library screening of GrB, we confirmed that it recognizes glutamic acid at P3 and shares this feature with caspases 10,17,22,29 . The carboxyl group of glutamic acid interacts with Lys192 and Asn218 in the GrB S3 pocket, consistent with GrB specificity.…”
Section: Discussionsupporting
confidence: 55%
“…These factors are consistent with known caspase active site inhibitors. The NSAID size restriction mirrors existing caspase inhibitors that often contain small core scaffolds (Poreba et al, 2015). It may be that larger NSAIDs are incapable of fitting into the S1 pocket, and are unable to compensate by forming sufficient contacts with the rest of the active site (Figure S2E).…”
Section: Resultsmentioning
confidence: 99%
“…Despite these functional differences, caspases are structurally analogous, posing a challenge for chemical targeting of individual caspases (Poreba et al, 2015; Wei et al, 2000). To explore NSAID specificity, we assayed the catalytic activity of caspases-1, -3, -4, -5, and -9 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…During the last step of apoptosis, caspase 3 cleaves one of its substrates, poly(ADP ribose) polymerase (PARP), after the DEVD (Asp–Glu–Val–Asp) sequence . This upstream sequence of the PARP cleavage site has been utilized as the basic scaffold for countless caspase 3 substrates, inhibitors, and activity‐based probes and in prodrug structures . Generally, in cancer lesions, caspase 3 is not active until it is activated by various antitumor stimuli (chemotherapy, radiation, etc).…”
Section: Peptide Prodrugsmentioning
confidence: 99%